1992
DOI: 10.3109/10715769209079517
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Destruction of Malarial Parasites by Polymorphonuclear Leucocytes and Oxidative Stress

Abstract: The role of reactive oxygen species (ROS) generated by polymorphonuclear leucocytes (PMNs) in the host response against malaria was investigated. Non-activated human PMNs were added to cultures of P. falciparum in microtitre cells. Parasite viability was evaluated by the incorporation of radioactive hypoxanthine. Using PMN/RBC = 1/150 (starting parasitemia was 1%) the incorporation on the second day in culture was only 61% of the control cultures. An effect could be observed already after two hours of incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Activated neutrophils and their secretory products may generate not only antiparasitic activity (16) but also endothelial damage (55), which can lead to organ failure in severe malaria. We have previously found that in synergism with neutrophils, sera from patients with complicated malaria damage endothelial cells in vitro (23).…”
mentioning
confidence: 99%
“…Activated neutrophils and their secretory products may generate not only antiparasitic activity (16) but also endothelial damage (55), which can lead to organ failure in severe malaria. We have previously found that in synergism with neutrophils, sera from patients with complicated malaria damage endothelial cells in vitro (23).…”
mentioning
confidence: 99%
“…Leukocytes from mice (9,25,43,44,62,71) and humans (2,12,23,49,58) infected with malaria show an increased ability to generate ROS. Leukocytes stimulated with malaria parasites in vitro generate ROS, and in some cases this has been linked to damage to the parasites in human (33,40,50) and murine (51) systems. However, ROS do not account for all the antimalarial activity of human leukocytes in such in vitro systems (41,50).…”
mentioning
confidence: 99%
“…Radicais oxidantes gerados em hemácias parasitadas também podem causar a elevação dos níveis de metemoglobina. Um estudo in vitro demonstrou haver elevação dos níveis de metemoglobina em hemácias parasitadas pelo Plasmodium falciparum 15 . O fato dos sujeitos desta pesquisa serem indivíduos com malária não interferiu nos resultados relacionados à metemoglobina circulante, pois nenhum destes apresentou malária grave.…”
Section: Discussionunclassified